Cultural Change in Iran: Women's Rights and the Middle Class - Zahirinejad, Mahnaz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The influence of Western culture and the efforts of domestic intellectuals merely scratched the surface of pre-existing and traditional practices towards women in nineteenth-century Iran. However, they led to the rise of social movements, such as the women's rights movement. Modernisation and economic growth drove ongoing processes of industrialization and urbanization during the twentieth century in Iran. Modernization also changed the social structure by creating a new middle class. It is expected that economic growth and educational attainment would empower the new middle class to demand greater political accountability, which, in turn, would lead to women's empowerment. The new middle class participated in the 1979 revolution, the outcome of which was to accelerate the rise of religious leadership. The revolutionary government renewed traditional Shiʿite practices, including traditional norms concerning women. Since the revolution, despite the imposition of Islamic law, the level of literacy and access to higher education, particularly for women, has escalated. This has led to women's awareness of their rights and their struggles to realize them in practice. However, unexpectedly, the new middle class hesitated in turning revolutionary and in joining the protestors. This research assumes that education enables women to confront their traditional roles in the family. Nevertheless, changing women's position is a process of cultural change that is coherent with both socio-economic development and the rise of a strong middle class.

Wpływ kultury zachodniej i wysiłki rodzimych intelektualistów zaledwie zarysowały powierzchnię tradycyjnych praktyk wobec kobiet w dziewiętnastowiecznym Iranie. Doprowadziły one jednak do powstania ruchów społecznych, takich jak ruch na rzecz praw kobiet. Modernizacja i wzrost gospodarczy napędzały trwające w XX wieku procesy industrializacji i urbanizacji w Iranie. Modernizacja zmieniła także strukturę społeczną, tworząc nową klasę średnią. Oczekiwano, że wzrost gospodarczy i wyższy poziom wykształcenia skłonią nową klasę średnią do żądania większej odpowiedzialności politycznej, co z kolei doprowadzi do wzmocnienia pozycji kobiet. Nowa klasa średnia uczestniczyła w rewolucji 1979 r., której rezultatem było ugruntowanie przywództwa religijnego. Rząd rewolucyjny odnowił tradycyjne praktyki szyickie, w tym tradycyjne normy dotyczące kobiet. Od czasu rewolucji, pomimo narzucenia prawa islamskiego, wzrósł poziom alfabetyzacji oraz dostęp do szkolnictwa wyższego, szczególnie dla kobiet. Doprowadziło to do obudzenia świadomości kobiet w zakresie ich praw i wysiłków zmierzających do ich realizacji w praktyce. Nieoczekiwanie jednak nowa klasa średnia wahała się przejść na stronę rewolucji i przyłączyć się do protestujących. W badaniu tym założono, że edukacja umożliwia kobietom skonfrontowanie się z ich tradycyjnymi rolami w rodzinie. Zmiana pozycji kobiet jest jednak procesem zmiany kulturowej, spójnym zarówno z rozwojem społeczno-gospodarczym, jak i powstaniem silnej klasy średniej.
Zmiany kulturowe w Iranie: prawa kobiet i klasa średnia
Keywords: Iran; Women; Middle Class; Culture; kobiety; klasa średnia; kultura